The Effect Of Internal Training Strategy On The Intention Of Working Turnover In Public Transport Companies (Field study in the General Company for Internal Transport in Lattakia) - Qasem, Samer A; Fayyad, Lina H; Maarouf, Hasan A (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to show the impact of the internal training strategy on the intention of the work turnover in the General Company for Internal Transport in Lattakia, through the knowledge of the impact of each of the training program plan, the implementation of training programs, and the efficiency of training programs, the researcher relied on the deductive approach as a general approach to research, and follow The survey methodology was distributed to 550 individuals, which represents the total staff of the company, and then conducted a field study to illustrate this relationship. The study concluded that there is an acceptable effect of the internal training programs plan on work intent and a weak non-significant effect of the implementation of the internship programs on work intent. He then presented a summary of the most important results reached, where the most important result was that there is an acceptable effect of internal training in the intention of work turnover through the plan of internship programs and efficiency of internship programs. هدفت هذه الدِّراسة إلى بيان تأثير استراتيجية التدريب الداخلي في نية دوران العمل في الشركة العامَّة للنقل الداخلي في اللَّاذقيَّة, من خلال معرفة تأثر كل من خطة برامج التدريب, تنفيذ برامج التدريب, وكفاءة برامج التدريب, وقد اعتمد الباحث على المقاربة الاستنباطيَّة كمنهج عام للبحث, واتباع منهجيَّة المسح, وقام بتوزيع الاستبانة على 550 فرد وهو يمثل مجموع كادر العاملين في الشركة، ومن ثمَّ أجرى دراسة ميدانيَّة بغرض بيان هذه العلاقة. وقد خلصت الدِّراسة إلى وجود تأثير مقبول لخطة برامج التدريب الداخلي في نية دوران العمل، ووجود تأثير غير معنوي ضعيف لتنفيذ برامج التدريب الداخلي في نية دوران العمل. ثمَّ قدَّم ملخص لأهم النتائج الَّتي تمَّ التَّوصُّل إليها, حيث كانت النتيجة الرئيسة الأهم هي أنَّ هناك تأثيراً مقبولاً للتدريب الداخلي في نية دوران العمل من خلال خطة برامج التدريب الداخلي وكفاءة برامج التدريب الداخلي.